Arabic Education and Modern Learning Construction in Muslim Minority Islamic Boarding School in Indonesia - Wekke, Ismail Suardi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2018)
AbstractIslamic boarding schools not only can bring up the religious enthusiasm, but also interpret Indonesia with a spirit of nationalism. Hence, it is not surprising that pesantren (Islamic Boarding School) is present to give a dedication to this nation aside from Islamic interest. Not only in the role of education,an educational institution like pesantren also had socio-cultural functions and role, a significant spiritual movement needs to be done to provide reinforcement towards empowerment within the goal of education holistically. A means that supports the learning process is the mastery of Arabic. This paper will describe the practice of Arabic teaching and learning in Muslim minority area with an approach to the principle of moderation. The research was carried out in West Papua which included five districts and one city. The results of the study showed that the application of learning that was carried out in Islamic boarding schools in Mayamuk, Aimas, Waisai, Teminabuan, Kaimana, Waigom, and Misol, was done in a well-structured. In the seven locations, Islamic education within the framework of the learning process that is based on language skills is carried out with the santri (Students) communicative approach.The skill of the students that is trained is linguistic expression without special emphasis on grammar mastery. The environment of boarding schools that provide dormitories as a place to live becomes a tool of interaction among santri (students) in practicing language skills. The language ability of the students is adapted to the learning context along with the environment. The existing social aspects are used to support the learning process. Finally, this research concludes that differences in learning objectives and determining approach and methodological aspects will affect learning Arabic.Keywords: Modern, Learning, Islamic Boarding School